Recent advances in the study of Spanish sociophonetic perception - Chappell, Whitney (Issues in Hispanic and Lusophone linguistics,, 2019)
"This book provides a cutting-edge exploration of the social meaning of phonetic variation in the Spanish-speaking world. Its 11 chapters elucidate the ways in which listeners process, perceive, and propagate phonetically motivated social meaning across monolingual and contact varieties, including the Spanish spoken in Spain (Asturias, Catalonia, and Andalusia), Ecuador, Colombia, Argentina, Chile, Mexico, and the United States. The book presents a wide variety of new and innovative research by renowned scholars, and the chapters examine issues like the influence of visual cues, bilingualism, contact, geographic mobility, and phonotactic predictability on social and linguistic perception. Additionally, the volume engages in timely discussions of intersectionality, replicability, and the future of the field. As the first unified reference on Spanish sociophonetic perception, this volume will be useful in graduate and undergraduate classrooms, in libraries, and on the bookshelf of any scholar interested in Spanish sociophonetics"--